2003
DOI: 10.1177/1534735403002002002
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Timing in Cancer Treatment: The Biological Foundation for an Integrative Approach

Abstract: Despite the many innovations that have occurred in cancer treatment, the age-specific mortality for most adult tumors has remained stable during the past 30 years. There have been clinically significant improvements in the outcomes of young and middle-aged patients, yet the vast majority of cancer patients are more than 50 years of age, among whom we observe few improvements in clinical outcomes. Clearly, many of today's cytotoxic agents have been shown to be effective in-vitro and in animal model systems; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Because cytokines that are produced by lymphocytes and macrophages are potent mediators of immune responses and the levels of individual cytokines can determine immune effector mechanisms, understanding immune-circadian clock control of specific immune mechanisms may have important clinical applications, such as optimization of the treatment of patients with septic shock, autoimmune diseases, and hematological diseases. As the toxicity and the antitumor efficiency of many traditional cytotoxic drugs in cancer therapy vary significantly with the time of day of drug administration (23), analysis of the circadian organization of physiological immune function not only might provide a better insight into the immune system in general, but also might offer a reduction in bone marrow toxicity and an increased intensity and improved efficiency of cytotoxic drugs for cancer patients.…”
Section: Vol 74 2006mentioning
confidence: 99%
“…Because cytokines that are produced by lymphocytes and macrophages are potent mediators of immune responses and the levels of individual cytokines can determine immune effector mechanisms, understanding immune-circadian clock control of specific immune mechanisms may have important clinical applications, such as optimization of the treatment of patients with septic shock, autoimmune diseases, and hematological diseases. As the toxicity and the antitumor efficiency of many traditional cytotoxic drugs in cancer therapy vary significantly with the time of day of drug administration (23), analysis of the circadian organization of physiological immune function not only might provide a better insight into the immune system in general, but also might offer a reduction in bone marrow toxicity and an increased intensity and improved efficiency of cytotoxic drugs for cancer patients.…”
Section: Vol 74 2006mentioning
confidence: 99%
“…These rhythms have direct and indirect implications for human heath. The metabolism and efficacy of drugs depends considerably on the time of day they are administered (Antoch et al, 2005;Halberg et al, 2006;Lis et al, 2003). Moreover, disruptions of the circadian clock have been shown to increase susceptibility to cancer, heart disease, and metabolic disorders while directly causing serious sleep disorders and influencing mental illness (Curtis and Fitzgerald, 2006;Halberg et al, 2006;Klerman, 2005;Levi and Schibler, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in cancer therapy, the circadian rhythms of metabolic enzymes and signal transduction proteins targeted by antitumor drugs influence the effect of these drugs (9)(10)(11). It has been suggested that administration of drugs at an appropriate time of the day could improve the outcome of pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%